Highly undersampled contrast‐enhanced MRA with iterative reconstruction: Integration in a clinical setting. Issue 6 (17th December 2014) - Stalder, Aurelien F.; Schmidt, Michaela; Quick, Harald H.; Schlamann, Marc; Maderwald, Stefan; Schmitt, Peter; Wang, Qiu; Nadar, Mariappan S.; Zenge, Michael O.
Abstract : Purpose: To integrate, optimize, and evaluate a three‐dimensional (3D) contrast‐enhanced sparse MRA technique with iterative reconstruction on a standard clinical MR system. Methods: Data were acquired using a highly undersampled Cartesian spiral phyllotaxis sampling pattern and reconstructed directly on the MR system with an iterative SENSE technique. Undersampling, regularization, and number of iterations of the reconstruction were optimized and validated based on phantom experiments and patient data. Sparse MRA of the whole head (field of view: 265 × 232 × 179 mm 3 ) was investigated in 10 patient examinations. Results: High‐quality images with 30‐fold undersampling, resulting in 0.7 mm isotropic resolution within 10 s acquisition, were obtained. After optimization of the regularization factor and of the number of iterations of the reconstruction, it was possible to reconstruct images with excellent quality within six minutes per 3D volume. Initial results of sparse contrast‐enhanced MRA (CEMRA) in 10 patients demonstrated high‐quality whole‐head first‐pass MRA for both the arterial and venous contrast phases. Conclusion: While sparse MRI techniques have not yet reached clinical routine, this study demonstrates the technical feasibility of high‐quality sparse CEMRA of the whole head in a clinical setting. Sparse CEMRA has the potential to become a viable alternative where conventional CEMRA is too slow or does not provide sufficient spatial resolution. Magn Reson Med 74:1652–1660, 2015. © 2014 Wiley Periodicals, Inc.